The export performance of rubber sector in Malaysia / Norhidayah Nordin (Faculty of Business and Management, 2007)
This study was conducted to examine the export performance of rubber sector in Malaysia. Thus according to Ministry of International Trade stated that Malaysia expects to maintain its position as the world's leading producer and exporter of natural rubber gloves catherers and latex thread in 2005. Moreover, demand for rubber product is expected to increase further, as a result of the projected growth in the electrical and electronics and automotive industries. The objective of this study is to examine the export performance of the five types of rubber which are the natural rubber, synthetic rubber, material of rubber, rubber tire and article of rubber from the year 2000 to 2006. Beside that this study also aims to study the trend of export of rubber. There are two methods of data analysis used in this study; the trend analysis and the Revealed Comparative Advantage (RCA) that provides a rough indicator of the strength of a product in terms of its comparative advantage in the world export market relative to others. This method consists of net export/total trade ratio and export performance ratio. For the trend analysis, researchers found out that the fluctuation happens on each types of rubber during the period of export performance. In addition, the trend also shows that the export and total trade of rubber are consistent. Among the five types of rubber trend, the natural rubber shows the highest increase in total trade and export from the year 2000 to 2006, which is from 2,913,933 to 2,332,113. This is followed by the material of rubber, synthetic rubber, article of rubber and rubber tire. Referring to the total trade/ net export, it is learnt that the material of rubber has the highest ratio. On the other hand, by using the export performance ratio, the result shows that the article rubber has the highest ratio, where the ratio of the natural rubber and the material rubber are below than one.